Refined energy-balance modelling of a supraglacial pond, Langtang Khola, Nepal - Miles, Evan S.; Pellicciotti, Francesca; Willis, Ian C.; Steiner, Jakob F.; Buri, Pascal; id_orcid:0 000-0003-3890-2109; Arnold, Neil S. (International Glaciological Society, 2016)
Supraglacial ponds on debris-covered glaciers present a mechanism of atmosphere/glacier energy transfer that is poorly studied, and only conceptually included in mass-balance studies of debris-covered glaciers. This research advances previous efforts to develop a model of mass and energy balance for supraglacial ponds by applying a free-convection approach to account for energy exchanges at the subaqueous bare-ice surfaces. We develop the model using field data from a pond on Lirung Glacier, Nepal, that was monitored during the 2013 and 2014 monsoon periods. Sensitivity testing is performed for several key parameters, and alternative melt algorithms are compared with the model. The pond acts as a significant recipient of energy for the glacier system, and actively participates in the glacier’s hydrologic system during the monsoon. Melt rates are 2-4 cm d-1 (total of 98.5 m3 over the study period) for bare ice in contact with the pond, and <1 mmd-1 (total of 10.6m3) for the saturated debris zone. The majority of absorbed atmospheric energy leaves the pond system through englacial conduits, delivering sufficient energy to melt 2612 m3 additional ice over the study period (38.4 m3 d-1). Such melting might be expected to lead to subsidence of the glacier surface. Supraglacial ponds efficiently convey atmospheric energy to the glacier’s interior and rapidly promote the downwasting process. ISSN:0260-3055 ISSN:1727-5644